Restoration of an academic historical gross pathology collection-refreshed impact on current medical teaching? - Eichhorn, Philip; Andraschke, Udo; Dross, Fritz; Geppert, Carol-Immanuel; Hartmann, Arndt; Rau, Tilman (Virchows Archiv, 2018)
The declaration of Leiden pronounces the demand to conserve pathological-anatomical collections as cultural heritage. Likewise, the Institute of Pathology of the Friedrich-Alexander-University Erlangen-Nuremberg owns macroscopic pathological-anatomical specimens reaching back over 150 years. The purpose of this work is to examine the impact, meaning, and perception of such historical preparations during the current medical curriculum. Additionally, the experiences from the renovation process can be used as a template for other institutes. All preparations were documented, photographed, and catalogued in an electronic database. During a restoration period, a series of didactically suitable specimens were professionally restored. Hereby, the help of a special course of interested students was admitted. In a second step, the specimens were integrated into the regular teaching of students in macroscopic pathology. An evaluation was carried out on two student cohorts with and without historical specimens by means of a questionnaire with 23 items and two free text fields. In total, 1261 specimens were registered covering diseases from almost the complete human body with a strong representation of the cardiovascular, urinary, gastrointestinal, and central nervous systems. Hereby, exceptional rare and untreated cases with medical relevance could be found and stepwise implemented into the curriculum. The student evaluation positively addressed that the courses became livelier and interactive. Furthermore, a more comprehensive overview and a better understanding of the macroscopic pathology were appreciated. However, more self-study time with the specimen was demanded. The authenticity of historical specimens contrasts with the tendency to carry out virtual "online" didactic methods. The stereoscopic view on often untreated and, therefore, unbiased cases enhances a skill-oriented deeper understanding of diseases. In conclusion, historical specimens regain interest and even didactic value, especially in an era of declining autopsy rates.
EVALuna2:34603